2019
DOI: 10.3390/ijms20205101
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Anti-Inflammatory, and Metabolic Properties of Tocopherols and Tocotrienols: Clinical Implications for Vitamin E Supplementation in Diabetic Kidney Disease

Abstract: Diabetes mellitus is a metabolic disorder characterized by the development of vascular complications associated with high morbidity and mortality and the consequent relevant costs for the public health systems. Diabetic kidney disease is one of these complications that represent the main cause of end-stage renal disease in Western countries. Hyperglycemia, inflammation, and oxidative stress contribute to its physiopathology, and several investigations have been performed to evaluate the role of antioxidant sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 56 publications
0
47
0
1
Order By: Relevance
“…Another study in Iran reported that dietary intake of vitamin E was associated with a decreased risk of incident CKD ( 21 ) . In human interventional studies, vitamin E supplementation decreased the risk of contrast-induced acute kidney injury in CKD patients and provided a positive effect on kidney function in diabetic patients ( 16 , 23 ) . On the other hand, there are some conflicting results on the association between vitamin E intake and kidney function ( 23 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study in Iran reported that dietary intake of vitamin E was associated with a decreased risk of incident CKD ( 21 ) . In human interventional studies, vitamin E supplementation decreased the risk of contrast-induced acute kidney injury in CKD patients and provided a positive effect on kidney function in diabetic patients ( 16 , 23 ) . On the other hand, there are some conflicting results on the association between vitamin E intake and kidney function ( 23 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In human interventional studies, vitamin E supplementation decreased the risk of contrast-induced acute kidney injury in CKD patients and provided a positive effect on kidney function in diabetic patients ( 16 , 23 ) . On the other hand, there are some conflicting results on the association between vitamin E intake and kidney function ( 23 ) . In addition, a recent epidemiological study reported that there was no association between serum vitamin E concentration and eGFR decline in young US adults ( 24 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The overproduction of these end-products and by-products of these pathways results in microvascular and macrovascular complications of diabetes [ 2 ]. Specifically, NFκB activation and PKC activation lead to abnormal upregulation of vascular and endothelial activity in renal glomeruli in diabetes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The role of vitamin E supplementation for metabolic diseases and diabetes-associated complications remains controversial. [ 3 ] The MICRO-HOPE study (2000) showed no significant renoprotective and cardioprotective outcomes with daily administration of tocopherol for 4.5 years [ 8 ]. A few systematic reviews concluded there was insufficient evidence to support the role of vitamin E as tocopherols for supplementation; there was no significant improvement in diabetic control as assessed by HbA1c levels and fasting sugar levels in the unselected population [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…(Middleton et al, 2000;Pavlova, 2016). Antioxidants (AOs) of natural origin such as quercetin (Quer) (Ozgen et al, 2016;Xu et al, 2019), curcumin (Cur) (Liu et al, 2017;Rachmani et al, 2018), vitamin E (Di Vincenzo et al, 2019), and coenzyme Q 10 (Tiano et al, 2007;Liu et al, 2016) may be effective for treating these pathologies. The high lipophilicity of these compounds, however, impedes their use as injectable preparations.…”
Section: Introductionmentioning
confidence: 99%